Stability Conditions for Wave Simulation in 3-D Anisotropic Media with the Pseudospectral Method (Communications in Computational Physics, 2012)
Simulation of elastic wave propagation has important applications in many area such as inverse problem and geophysical exploration. In this paper, stability conditions for wave simulation in 3-D anisotropic media with the pseudospectral method are investigated. They can be expressed explicitly by elasticity constants which are easy to be applied in computations. The3-D wave simulation for two typical anisotropic media, transversely isotropic media and orthorhombic media, are carried out. The results demonstrate some satisfactory behaviors of the pseudospectral method.